Questions about the Study of Cai Yuanpei and Peking University Before and After the May Fourth Movement : A Revision Based on Primary Historical Materials - Piyasirikul, Kampol (Journal of Sinology (วารสารจีนวิทยา), 2015)
During the past several decades, there have been a number of research works relating to Cai Yuanpei and Peking University, before and after the May Fourth Movement. However, the academic world has different perspectives towards these works and divides them into the three following issues: 1) Cai Yuanpei’s service as the President of Peking University, 2) Cai Yuanpei’s attitudes towards the May Fourth Movement, and 3) Cai Yuanpei’s resignation. In the past, the writer studied, summarized the mentioned three issues, and published an article without using any primary historical materials to analyze them. In order to improve the study of Cai Yuanpei and to clarify those three issues, the writer has re-analyzed them based on relavant primary historical materials. Consequently, basing on the study of the related research papers, the writer has raised some new viewpoints to make this current research ahead of others and as close as possible to the perfection.